Serum levels of immunoglobulin G and M antibodies against SARS-CoV-2 in asymptomatic individuals prior to COVID-19 vaccination in the Democratic Republic of Congo - Eric Kasongo Mukenge; Christian Nsimba Lengo; Blaise Matondo-Manzambi Sumbu; Jérémie Masidi Muwonga; Jean-Robert Rissassi Makulo; Mamy Zita Ngole; Ben Izizag Bepouka; Guyguy Kamwiziku; Hippolyte Nani-Tuma Situakibanza; Mireille Nkanga Nganga; Gustave Ntita Ilunga; Fonce Tshibawu Nkunda; et al. (PLoS ONE, 2026)
Despite the production of protective cross-reactive antibodies during COVID-19, data on immunoglobulin G (IgG) and immunoglobulin M (IgM) levels prior to vaccination remain limited in the Democratic Republic of Congo (DRC). This study aimed to assess serum IgG and IgM antibodies against SARS-CoV-2 in asymptomatic individuals COVID-19 vaccination in the DRC. A total of 1,500 individuals who presented for COVID-19 vaccination at the University Clinics of Kinshasa between April 19 and December 31, 2021, were included. The mean age was 47.5 ± 16.0 years, with a predominance of males (69.4%, sex ratio 2:1). Prior to vaccination, 38.8% of participants had elevated IgG levels, while 32.9% had elevated IgM levels. After multivariable adjustment, female sex (adjusted odds ratio [aOR] 1.54; 95% confidence interval [CI] 1.14–2.46), non-healthcare professional status (aOR 2.24; 95% CI 1.42–3.58), and the absence of comorbidities (aOR 2.33; 95% CI 1.38–3.71) remained independently associated with IgM seropositivity. Overall, IgG and IgM seroprevalence were high prior to vaccination. IgM positivity was associated with specific sociodemographic, biochemical, and hematological profiles. These findings highlight the importance of routine serological surveillance before vaccination to better understand infection dynamics and to inform public health interventions.